Pengaruh Literasi Keuangan Terhadap Perilaku Keuangan Mahasiswa - Indra Putri, Wayan Tari; Sumiari, Kadek Nita (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.10.NO.03.TAHUN. 2021, 2021)
Having knowledge of financial literacy is a must in order to have a prosperous life. Currently the OJK is working to improve financial inclusion and literacy, especially among students. This step is a form of effort to increase the role of students in the Indonesian economy. As the next generation, a student must have knowledge related to personal financial management. This knowledge will be very useful for students to manage their finances in the future. Four diploma students majoring in Accounting at the Bali State Polytechnic have obtained courses related to finance and investment so that they should have a good level of financial literacy knowledge. The purpose of this research is to examine the effect of financial literacy on student financial behavior. Respondents in this study amounted to 95 people. The data in this study were analyzed using simple linear regression analysis. The results of this study are that there is an influence between financial literacy variables on student financial behavior. The test results show that the better the knowledge or understanding of financial literacy possessed by students, the better the student's ability to implement good financial behavior.